2011
DOI: 10.1007/s10551-011-1061-0
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Human Resource Management Systems to Cope with Diversity

Abstract: The purpose of this study is to examine how workgroup diversity can be managed through specific strategic human resource management systems. Our review shows that 'affirmative action' and traditional 'diversity management' approaches have failed to simultaneously achieve business and social justice outcomes of diversity. As previous literature has shown, the benefits of diversity cannot be achieved with isolated interventions. To the contrary, a complete organizational culture change is required, in order to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 142 publications
0
21
0
Order By: Relevance
“…Johns et al (2012) argue that a business case hardly applies to public sector institutions, thus seeking to justify diversity considerations in advancing moral, deontological arguments. Martin-Alcàzar et al (2012) underscore the deficiencies of traditional diversity management practices in simultaneously meeting business and social justice diversity outcomes: they then argue in favor of an overall organizational culture change entailing various HRM systems' transformation in view of effectively coping with diversity on the grounds of appreciating individual differences. Perriton (2009) argues that the business case constrains the discussion of social justice issues at the workplace, thus entailing an inadequate response to justice concerns: market processes tend to produce JOCM 26,6 discrimination, not equity leading to women's unequal position in a work setting.…”
Section: Rationales For Managing Diversitymentioning
confidence: 94%
“…Johns et al (2012) argue that a business case hardly applies to public sector institutions, thus seeking to justify diversity considerations in advancing moral, deontological arguments. Martin-Alcàzar et al (2012) underscore the deficiencies of traditional diversity management practices in simultaneously meeting business and social justice diversity outcomes: they then argue in favor of an overall organizational culture change entailing various HRM systems' transformation in view of effectively coping with diversity on the grounds of appreciating individual differences. Perriton (2009) argues that the business case constrains the discussion of social justice issues at the workplace, thus entailing an inadequate response to justice concerns: market processes tend to produce JOCM 26,6 discrimination, not equity leading to women's unequal position in a work setting.…”
Section: Rationales For Managing Diversitymentioning
confidence: 94%
“…Yet little research has examined how performance consideration is reflected in the adoption of DEMS. We have limited guidance on what types of DEM practices are useful and limited theorizing about how DEM practices should fit with the environment, with internal organizational characteristics, or with each other (Martín‐Alcázar, Romero‐Fernández, & Sánchez‐Gardey, ).…”
mentioning
confidence: 99%
“…This can make it difficult to retain a diverse workforce in the organizations. The benefits of workforce diversity stated in the literature ‘cannot be achieved with isolated interventions…[rather] a complete organizational culture change is required, in order to promote appreciation of individual differences’ (Martín-Alcázar et al, 2012: 511). Furthermore, intergroup relationship factors such as prejudice, stereotyping and discrimination (as found in this research) can lead to the provision of a low quality service (Seeleman et al, 2015) or underutilization of services (as found in the case of stigmatized services).…”
Section: Discussionmentioning
confidence: 99%